2021
DOI: 10.7196/samj.2021.v111i3.15263
|View full text |Cite
|
Sign up to set email alerts
|

Drastic reduction of orthopaedic services at an urban tertiary hospital in South Africa during COVID-19: Lessons for the future response to the pandemic

Abstract: This open-access article is distributed under Creative Commons licence CC-BY-NC 4.0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…These findings were valid for pediatric and adult populations across specialty clinics [ 20 22 ]. Moreover, reports from South Africa also showed a drastic decrease in outpatient visits [ 23 ] and a substantial decrease in the number of patients presenting to the emergency care during the lockdown period due to COVID 19 [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings were valid for pediatric and adult populations across specialty clinics [ 20 22 ]. Moreover, reports from South Africa also showed a drastic decrease in outpatient visits [ 23 ] and a substantial decrease in the number of patients presenting to the emergency care during the lockdown period due to COVID 19 [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our data was consistent with our colleagues in Cape Town, comparing a tertiary hospital in Cape Town to one in Johannesburg; however, our study further looked at the availability and prohibition of alcohol, and the effects thereof. 25 Our study showed a significant increase in admissions of 112% from when alcohol was banned in alert level 4, to when it was available in alert level 3 (3a) (Figure 4). The change in admissions between alert levels 4, 3 (3a) and 3 (3b) suggests the influence alcohol has on orthopaedic trauma.…”
Section: Discussionmentioning
confidence: 58%
“…[7,8] The restrictions were relaxed to some extent with migration to level 4 lockdown on 1 May 2020, and were eased further under level 3 on 1 June, when the sale of alcohol was permitted between Monday and Thursday, during daytime only. [9] Navsaria et al [10] and Waters et al [11] reported a decline in trauma cases in Cape Town during the hard lockdown period, but we are not aware that the situation has been evaluated in the northern part of SA.…”
Section: Researchmentioning
confidence: 99%